(untitled) (Neo Science Peer Reviewed Journal, 2023)
In this article the inner pattern of semantical-structure on the basis of linguistic approach is examined deeply. It is identified the integration of both semantical layer and structure borrowed words (muse, combine, sport, paynet) in Karakalpak language.